Sawfly egg deposition extends the insect life cycle and alters hormone and volatile emission profiles - Dávila, Camila; Fiorenza, Juan E.; Gershenzon, Jonathan; Reichelt, Michael; Zavala, Jorge A.; Fernández, Patricia C. (Frontiers in Ecology and Evolution, 2023)
Insect oviposition can enhance plant defenses and decrease plant quality in response to future feeding damage by hatched larvae. Induced resistance triggered by egg deposition and its negative effect on insect herbivore performance is known for several annual plants but has been much less studied in woody perennials, such as species of the Salicaceae. Here we studied the response of the willow Salix babylonica to oviposition by the specialist willow sawfly Nematus oligospilus and its impact on insect performance. We measured the effect of oviposition on larval feeding and pupa formation and evaluated its influence on plant phytohormones and volatile emission profile. Our results showed that oviposition reduced neonate larval growth and increased the proportion of prepupae that delayed their transition to pupae, thus extending the length of the sawfly cocoon phase. Oviposited willows increased jasmonic acid levels and changed their volatile profile through enhanced concentrations of the terpenoids, (E/E)-α-farnesene, (Z)- and (E)-β-ocimene. Volatile profiles were characteristic for each type of insect damage (oviposition vs. feeding), but no priming effect was found. Our results demonstrate that willows could perceive sawfly oviposition per se as a primary factor activating defense signaling via the jasmonic acid pathway. This induced response ultimately determined changes in pupation dynamics that may affect the whole insect population cycle.